2017
DOI: 10.1038/mp.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomic, epigenetic and genetic differences in monozygotic twins discordant for attention deficit hyperactivity disorder

Abstract: The study of monozygotic twins discordant for Attention Deficit Hyperactivity Disorder can elucidate mechanisms that contribute to the disorder, which affects around 7% of children. First, using in vivo neuroanatomic imaging on 14 pairs of monozygotic twins (mean age 9.7, standard deviation 1.9 years), we find that discordance for the disorder is mirrored by differing dimensions of deep brain structures (the striatum and cerebellum), but not the cerebral cortex. Next, using whole blood DNA from the same twins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…This is consistent with the finding that the psychostimulant methamphetamine, which induces hyperactivity in rodents, also induces Dnmt1 mRNA levels in the rodent brain (Numachi et al, 2007). In addition, an increased Dnmt1 expression has been found in psychosis (Veldic et al, 2005) and DNA methylation changes have been reported in many neuropsychiatric disorders including schizophrenia (Grayson and Guidotti, 2013) and ADHD (Chen et al, 2018;Heinrich et al, 2017), further providing a possible link between Dnmt1 dysregulation and the hyperactivityrelated phenotype observed in our double-hit stress group.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the finding that the psychostimulant methamphetamine, which induces hyperactivity in rodents, also induces Dnmt1 mRNA levels in the rodent brain (Numachi et al, 2007). In addition, an increased Dnmt1 expression has been found in psychosis (Veldic et al, 2005) and DNA methylation changes have been reported in many neuropsychiatric disorders including schizophrenia (Grayson and Guidotti, 2013) and ADHD (Chen et al, 2018;Heinrich et al, 2017), further providing a possible link between Dnmt1 dysregulation and the hyperactivityrelated phenotype observed in our double-hit stress group.…”
Section: Discussionsupporting
confidence: 91%
“…The first and only study to examine ADHD cases directly, was a small study by our group 31 . That study of 105 children was able to replicate suggestive findings in MYT1L and VIPR2, also a top hit in an EWAS of environmental exposure 28 and a recent twin study 32 . An EWAS of ADHD symptoms in adult population cohorts reported additional novel candidate sites for exploration, as well as noting that most top-ranked loci were driven by DNA methylation quantitative trait loci (mQTL) 33 .…”
Section: Introductionmentioning
confidence: 76%
“…First, our previous report of lower DNA methylation in VIPR2 in never-medicated boys 31 was supported in a targeted analysis after removing children used in our prior report, although at a smaller effect size, suggesting that this sex-specific effect is reproducible. Sites annotated to VIPR2 have also been identified as differentially methylated in two other studies of ADHD 28,32 , but with effects varying in direction. Given that we observe a sex-specific effect in VIPR2 (hypomethylation in male cases, and hypermethylation in female cases) and other studies did not stratify by sex, it is possible that the inconsistencies across studies related to the direction of effect are due to differences in the sex ratio of the samples studied.…”
Section: Discussionmentioning
confidence: 93%
“…Heritability (h 2 ) of the disorder is estimated at 0.75–0.917 and many genetic variants, often related to neurotransmission and neurodevelopment,8 9 are associated with an increased risk of developing ADHD 10 11. Epigenetic regulation of gene activity, such as differential DNA methylation of genes related to neurotransmission,12 neurodevelopment and peroxisomal processes, is also associated with ADHD 13. Environmental risk factors of ADHD include pre, peri and postnatal factors, such as prematurity, low birth weight, in utero exposure to smoking, alcohol and drugs, psychosocial conditions and diet 14 15.…”
Section: Introductionmentioning
confidence: 99%